561 ENHANCING RADIATION-INDUCED IMMUNOGENICITY IN THE MULTIMODAL TREATMENT OF ESOPHAGEAL CANCER: IS HYPOFRACTIONATION THE ANSWER?. (14th September 2020) - Donlon, N; Davern, M; Sheppard, A; Elliott, J; Ravi, N; Donohoe, C; Reynolds, J; Lysaght, J
Abstract: : Esophageal adenocarcinoma (EAC) is increasing exponentially year on year in Western civilisation, linked epidemiologically to GERD and obesity. It is characterized by a highly immunosuppressive tumour microenvironment (TME) and evasion of immune surveillance. A novel treatment option is upregulating immune mediated anti-tumour response via Immune Checkpoint Blockers (ICB). Methods: The effects of immune checkpoint blockers were characterised in terms of proliferation, cytolysis and cancer cell viability. The basal expression of immune checkpoints (TIGIT, PD-1, PD-L1, PD-L2) and Damage Associated Molecular Patterns (Calreticulin, HMGB1) in EAC patients was profiled ex vivo using fresh tumor, blood and lymph-node tissue (n = 10) by flow cytometry. In an in-vitro study, T-lymphocytes were isolated and treated with Nivolumab, Pembrolizumab or Atezolizumab, activated and co-cultured for 48 hours with a panel of four esophageal cancer cell lines; OE33P, OE33R, FLO-1, FLO-1LM treated with 1.8Gy and 3.6Gy of radiation (Fig 1). Cytolysis was measured using a CCK8 assay.(n = 6). Results: The expression of TIGIT, TIM-3, PD-1 and its ligands (PD-L1, PD-L2) were higher (p < 0.001) in EAC patients compared to age matched healthy controls. Similarly, when mimicking conditions of the TME including nutrient deprivation and hypoxia, this results in a significant (p < 0.001) increase in DAMP and ICB expression on CD3, 4 and CD8 T cells in the TME when treated with radiation. T-lymphocytes induced by checkpoint blockers plus ionising radiation directly to the tumor resulted in the best repression of tumour growth with 3.6Gy inducing the highest rate of cytolysis (p < 0.001). ICB and radiation resulted in reduced cancer cell viability and proliferation. Conclusion: Fractionated radiation can enhance immunologic function. In combination with ICB, this symbiotic relationship enhances the cytotoxic potential of T lymphocytes with conventional dosing, however, with hypofractionation, this signifies true immunogenicity, and as such this provides a basis for advocating for potential combination strategies with ICB in the multimodal treatment of EAC.